Reflections on the IATEFL Research Special Interest Group Pre Conference Event ‘Communicating and Learning from Research’(Liverpool, 2019) - Kakoulli-Constantinou, Elis (My University, 2019)
In today’s world where researching, questioning, interpreting and synthesising information are among the most important skills that an individual needs to possess, teacher research is considered to be one of the best practices that lead to teacher learning and professional development (Dikilitaş & Yaylı, 2018; Gallagher-Brett, 2019; Rebolledo, Smith & Bullock, 2016; Snoek & Moens, 2011). The benefits of teacher research as well as the dynamic interaction between academics and teachers in relation to research constituted the focus of the IATEFL Research Special Interest Group (ReSIG) Pre-Conference Event at the IATEFL 2019 conference in Liverpool. The event, which I had the pleasure of attending, was entitled ‘Communicating and Learning from Research’, and was truly a success.